2018
DOI: 10.1002/adem.201801113
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Anisotropy Investigated in the Complex SLM‐Processed Sc‐ and Zr‐Modified Al–Mg Alloy Microstructure

Abstract: Additive manufactured Sc-modified aluminum alloys hold great promise for aerospace components under high and/or complex loads. While the thermal patterns formed in the melt pool during selective laser melting (SLM) of the powdered material result in a complex microstructure featuring a bimodal grain size distribution, such alloys show an isotropic mechanical response during mm-scale testing. To understand the role of microstructure on the mechanical response, nanoindentation is performed on SLM-processed Scalm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…To investigate a complete SLM processing window for relative densities exceeding 99%, a second build job will be performed with differing energy volume densities and respective scan speeds of 30, 45, 60, 80, 100 J/mm3 and 2962, 1975, 1481, 1111, 889 For each of the five sets of SLM process parameters, one cube sample on 3mm high support structures were built (figure 1), whereby 5 cube samples were built in one build job. Anisotropy is not investigated in this paper as both Schmidtke et al (2011) and Best et al, (2018) have indicated that anisotropy is very low for Scalmalloy, therefore all samples were built in a line parallel to x-direction with 20mm distances in between each cube and centered on the build platform.…”
Section: Proceeding Parameter For Slm Windowmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate a complete SLM processing window for relative densities exceeding 99%, a second build job will be performed with differing energy volume densities and respective scan speeds of 30, 45, 60, 80, 100 J/mm3 and 2962, 1975, 1481, 1111, 889 For each of the five sets of SLM process parameters, one cube sample on 3mm high support structures were built (figure 1), whereby 5 cube samples were built in one build job. Anisotropy is not investigated in this paper as both Schmidtke et al (2011) and Best et al, (2018) have indicated that anisotropy is very low for Scalmalloy, therefore all samples were built in a line parallel to x-direction with 20mm distances in between each cube and centered on the build platform.…”
Section: Proceeding Parameter For Slm Windowmentioning
confidence: 99%
“…Lastly, a hyper eutectic Al-Sc composition was attained. Best et al (2018) studied the mechanical anisotropy for the bi-modal microstructure of Scalmalloy. Anisotropy was low on a macroscopic scale, and although some microscopic discrepancies were found, these could be improved with annealing further supporting 1 st ICESET 2020 23 Schmidtke et al (2011) findings.…”
Section: Introductionmentioning
confidence: 99%
“…For example, compared with the samples fabricated by the casting process, the Al-0.5% Sc alloy fabricated by SLM exhibits a finer grain size and better mechanical properties, and with the average grain size decreased from 25 to 7 µm, the yield stress has been increased from 131 to 323 MPa, and the elongation has been increased from 3.7 to 10.5%, respectively [22]. Moreover, the grain size and microstructure feature could be altered by changing the 3D printing parameter and thus the mechanical properties of the 3D-printed materials could be affected [20,[23][24][25][26][27]. In our previous study, we showed that the grain size can be reduced and the columnar grain can be limited by adjusting parameters and thus significantly improve the yield stress and elongation of the 3D-printed Scalmalloy [19].…”
Section: Introductionmentioning
confidence: 99%